2013
DOI: 10.1089/tmj.2012.0109
|View full text |Cite
|
Sign up to set email alerts
|

HONEY: A Multimodality Fall Detection and Telecare System

Abstract: ABSTRACT-The increasing cost of finance and healthcare resources is driving healthcare providers to provide home-based telecare instead of institutionalized healthcare. Falling is one of the most common and dangerous accidents for elderly group and a significant factor affecting the living quality of the elderly. Many efforts have been put towards providing a robust method to detect falls accurately and timely. To facilitate a reliable, safe and real-time home-based healthcare environment, we propose the HONEY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…The family healthcare network consisting of Fallsensor and Homeserver, responds to collection of alarm information and transmits those data to CloudPIS. CloudPIS is an information-sharing platform for patients and caregivers [13]. Then, a remote monitoring center or caregivers can obtain related data from CloudPIS, so that one can be helped in time once an emergency occurs.…”
Section: Design Of System Architecturementioning
confidence: 99%
“…The family healthcare network consisting of Fallsensor and Homeserver, responds to collection of alarm information and transmits those data to CloudPIS. CloudPIS is an information-sharing platform for patients and caregivers [13]. Then, a remote monitoring center or caregivers can obtain related data from CloudPIS, so that one can be helped in time once an emergency occurs.…”
Section: Design Of System Architecturementioning
confidence: 99%
“…If an extra fall detection app is running permanently on the phone, this typical lifespan of 24 h could be lessened. In fact, according to certain questionnaires fulfilled by the volunteers of a real life trial of an FDS [24], FDSs should be operative for at least six months with no battery recharge in order to be considered satisfactory by the users (an autonomy which is obviously far from the actual features of current devices).…”
Section: Consumption In Smartphone-only Based Architecturesmentioning
confidence: 99%
“…Research has shown that weight scales transmit data to a mobile smartphone that forwards the information to a cloud based server, so that clinicians can assess weight management in youth [8]. Smartphones sync with the cloud servers to monitor fall detection in elderly individuals [9]. These few examples show that how wearable or devices used by the person interact with smartphone or phones to send information to remote servers.…”
Section: B Internet-connected Gatewaysmentioning
confidence: 99%